[en] INEQUALITIES IN THE CENTER OF THE CLEAVED CITY: MEANINGS OF WORK AMONG YOUNG PEOPLE FROM DIFFERENT SOCIAL CLASSES - DANIEL OSWALDO SANTANA DE SOUZA (MAXWELL, 2018)
[pt] Esta tese teve como objeto de pesquisa a associação de aspectos econômicos e sociais ao fenômeno da dotação de sentidos ao trabalho. Considerados de forma articulada, tais aspectos viabilizam a observação do trabalhador como um ser social, passível de uma análise sob a perspectiva teórica de classes. A Teoria dos Condicionantes Sociais, de Pierre Bourdieu (2015), destacou-se como uma lente teórica útil na consideração deste objeto de pesquisa. Estabelecido o recorte de pesquisa - jovens trabalhadores do Centro do Rio de Janeiro - os objetivos deste estudo: a) compreender como se dá a dotação de sentidos ao trabalho entre jovens de diferentes classes sociais; b) remontar as origens do sentido do trabalho comuns a cada classe social entre os jovens; e c) identificar os condicionantes sociais do campo profissional referentes à cada classe social. Foram realizadas 18 entrevistas em profundidade com jovens trabalhadores que, para efeitos de análise, foram divididos em dois grupos: jovens zona norte - de estratos sociais menos abastados; e jovens zona sul – de estratos sociais mais afluentes. Em linhas gerais, nos dois grupos destacou-se a percepção do trabalho como uma forma de subsistência. Entre os jovens zona norte, a atividade profissional é carregada de forte sentido moral, já dentre os jovens zona sul, consideram-se também aspectos hedonistas referentes ao trabalho, que seria o exercício de uma vocação, dotada com uma função de relevância e impacto social. O cotidiano profissional e a família emergem como categorias que explicam a origem dos sentidos atribuídos ao trabalho para esses dois grupos. Todavia, dentre os jovens zona sul, depreende-se a percepção de que tal construção se daria de forma reflexiva, sendo ponderado por seus próprios valores e crenças. A socialização primária dos jovens zona norte é marcada por uma considerável fragilidade da sua experiência escolar e familiar - no sentido de provisão material. Em contraponto, os jovens zona sul gozam de uma experiência escolar axiomática e amplo suporte familiar. === [en] This thesis is about the association of economic and social aspects to the meaning of work phenomena. Considered in an articulated way, these aspects enable the observation of the worker as a social agent, through the theoretical perspective of social classes. Pierre Bourdieu s Theory of Social Conditioning stood out as a theoretical lens useful in the consideration of this object of research. Once stablished one specific group of interest – young workers at the Center of Rio de Janeiro City – the research objectives were: a) understand how the meaning of work phenomena happens among young workers from different social classes; b) set back the sources of meaning of work common to each social class; and c) identify the social determinants of the professional field related to each social class. Eighteen in-depth interviews were carried out with young workers who, for the purposes of analysis, were divided into two groups: north zone - concerning less well-off social strata; and south zone - concerning more affluent social strata. In general, the two groups emphasized the perception of work as a form of subsistence. Among the young people from the north zone group, professional activity has a strong moral sense, and among the ones from the south zone group, some hedonistic aspects are related to work, which would also be the performance of a vocation, endowed with a social function of relevance and impact. Work context and the family emerge as categories that explain the sources of the meanings attributed to work for both groups. However, among the subjects from the south zone group, there is a perception that such construction would take place in a reflexive way, being filtered by its own values and beliefs. The primary socialization of the young workers from the north zone group is marked by a considerable fragility of their scholar and familiar experience - in the sense of material provision. In contrast, the subjects from the southern zone group enjoy an axiomatic school experience and broad family support.